Experimental analysis of acidizing in Weizhou X low permeability reservoir - Yi Zhang; Bin Zhang; Feng Wei; Hongjun Lu; Banghua Liu; Mingguang Tang; PengYu Zhu; Rui Wang; Jian Yan (Engineering Reports)
Abstract Aiming at the problem of increased water injection pressure and poor water injection effect during the water injection operation of Weizhou X offshore low permeability oil reservoir. The cause of clogging was clarified using cast thin section experiments, water quality compatibility experiments and reservoir sensitivity experiments, and corresponding deblocking agents were configured based on the experimental results. The experimental results show that Weizhou X oilfield has strong velocity sensitivity (damage rate 85.35%) and strong salt sensitivity (damage rate 63.02%), and there is a phenomenon of water quality incompatibility. Analysis shows that the excessive velocity of the injected water causes the core particles to fall off and the water quality is incompatible with the calcium carbonate precipitation to cause pore throat blockage as the fluid migrates to the small roar, which is the main reason for the increase in water injection pressure. Based on the analysis results, the acid solution formula was optimized and determined to be: 12% HCl + 0.5% HF + 3% CH3COOH + 0.5% C6H12N4. Indoor test results show that the acid has good clay swelling prevention and reservoir modification effects, and the average reservoir modification rate is 129.21%. The plug‐removing effect is remarkable and can be promoted in similar oil fields.